The impact of training and retraining of police officers on their competitiveness - Y. Y. Podorozhnii (Law and Safety)
Based on the analysis of scientists’ scientific views, the meaning of the concept of “qualification” has been revealed. It has been found that the qualification is a complex characteristic of the employee, which includes the presence of the appropriate level of education, as well as professional skills, abilities, skills, experience in performing certain processes and actions, which together characterize them as an experienced subject of a certain type of work. In fact, qualifications are a factor that determines whether a person can perform a job, such as serving in the police.